Intraoperative Photodynamic Diagnosis Using Talaporfin Sodium Simultaneously Applied for Photodynamic Therapy against Malignant Glioma: A Prospective Clinical Study - Shimizu, Kazuhide; Nitta, Masayuki; Komori, Takashi; Maruyama, Takashi; Yasuda, Takayuki; Fujii, Yu; Masamune, Ken; Kawamata, Takakazu; Maehara, Taketoshi; Muragaki, Yoshihiro (Frontiers in Neurology, 2018)
Objective The goal of this study was to demonstrate the feasibility of intraoperative photodynamic diagnosis (PDD) of malignant glioma using the fluorescence from talaporfin sodium (TS), which is used simultaneously for photodynamic therapy (PDT). Methods Patients with suspected primary malignant glioma who were eligible for surgical removal of the tumor and PDT with TS were enrolled in this prospective study. Tissue samples were obtained from the contrast-enhanced (CE) region and from the surrounding non-contrast-enhanced (NCE) marginal tissue at the boundary between the tumor and normal tissue. The excised samples were set into a fluorescence measurement system, which consisted of a semiconductor laser with a 400-nm wavelength for excitation, and a compact spectrometer for detection, which were applied and received through a custom-made probe consisting of coaxial optical fibers. The fluorescence spectrum was obtained and peak intensity was calculated. Tumor cellularity was histopathologically analyzed and semi-quantitatively classified into four (0-3) categories. Results Eighty-six samples from 17 surgical cases were available for fluorescence measurement and analysis. The fluorescence from TS had a single peak at 664 nm that was easily distinguished from the 400-nm excitation light. Samples from the CE regions showed higher fluorescence intensity than those from the NCE regions (P<0.001). DAPI staining and fluorescence microscopy confirmed that cells in the CE regions showed red fluorescence in their cytoplasm. The fluorescence was notably strong along vascular endothelium. CE samples from newly diagnosed versus recurrent cases showed no difference in fluorescence intensity (P=0.26). Among all samples (CE and NCE combined), the fluorescence intensity was very high in those of histopathological class 3, and a trend of increased fluorescence according to histopathological class (P<0.001) was shown. Differences between class 0 and 3 (P<0.001), class 1 and 3 (P<0.001), and class 2 and 3 (P=0.018) were significant. Conclusion Intraoperative simultaneous PDD and PDT with TS can be performed for patients with malignant glioma. The blue excitation light that is used for 5-aminolevulinic acid PDD can be used for our technique (TS-PDD). The strong fluorescence from pathologically malignant tissues may be due at least in part to the involvement of microvascular structures.